New British fascism : rise of the British National Party - Goodwin, Matthew J. 1981- (Routledge studies in extremism and democracy, 2011)
The legacy of history -- In the ghetto : 1982-1999 -- From street gang to political party : 1999-2009 -- Organizing for elections -- Voting for the BNP -- Membership -- Initial motivations : why join? -- Sustaining commitment : why stay? -- Conclusions : yet another false dawn?